Gender Revolution in a Malthusian Utopia: Harriet Martineau’s world of Garveloch - Catherine Heyrendt-Sherman (Cahiers Victoriens et Edouardiens)
Harriet Martineau (1802–1876), sociologist, historian and novelist, was also a talented populariser. Illustrations of Political Economy (1832–1834) is her attempt to make Malthusian and Ricardian theories accessible to all, through the use of fiction. Two of the twenty-five tales featured take place in Garveloch, a remote Scottish island which provides the setting for a socio-demographic experiment. The paper shows how Martineau set up a colourful Malthusian utopia that also challenged traditional gender roles. Her Autobiography suggests that she knowingly took a calculated risk, incurring the wrath of the Tory press. In particular, the empowerment of female characters, able to discuss birth control and decide against matrimony, was in breach of Victorian values. Undeterred by her detractors, Martineau carried on as a pioneer and political activist.